Exploring the inherent mechanism of residents’ participation behavior in neighborhood regeneration projects: an empirical study using an extended IMB model in China - Fu, Xinyue; Zhuang, Taozhi; Huang, Ruopeng; Dong, Yaxian (Frontiers in Psychology, 2023)
Introduction Resident participation has gained increasing prominence and significance in the pursuit of sustainable neighborhoods regeneration. However, the current state of resident participation practices remains beset by several challenges, which present formidable impediments to the initiation and execution of neighborhood regeneration initiatives. This study aims to investigate the underlying mechanisms of residents’ participation behavior to enhance resident participation in neighborhood regeneration projects. Methods The present study employs the extended Information-Motivation-Behavioral (IMB) model to examine the determinants and mechanisms influencing residents’ willingness and participation in neighborhood regeneration projects, with a specific focus on the Chinese context. Drawing upon data from 477 meticulously validated questionnaires administered to residents, the study applies structural equation modeling (SEM) to unravel the intrinsic dynamics of residents’ participation behavior. Results The empirical findings of this research reveal that information, motivation, and the perceived local government support all exert a significant impact on residents’ participation willingness. Notably, motivation emerges as the most influential factor. Discussion This study uncovers a direct influence of local government organizations on both residents’ willingness and their actual participation, suggesting that government organizations can spearhead innovative strategies to bolster residents’ willingness and furnish avenues for translating willingness into tangible participation. The outcomes of this study furnish an indispensable theoretical framework and offer policy recommendations that hold paramount importance for the deployment of novel interventions geared toward stimulating active involvement of residents in neighborhood regeneration.